2014
DOI: 10.1155/2014/407832
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Gas Emissions from Cotton Field under Different Irrigation Methods and Fertilization Regimes in Arid Northwestern China

Abstract: Drip irrigation is broadly extended in order to save water in the arid cotton production region of China. Biochar is thought to be a useful soil amendment to reduce greenhouse gas (GHG) emissions. Here, a field study was conducted to compare the emissions of nitrous oxide (N2O) and methane (CH4) under different irrigation methods (drip irrigation (D) and furrow irrigation (F)) and fertilization regimes (conventional fertilization (C) and conventional fertilization + biochar (B)) during the cotton growth season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Despite limited impacts on grain yield in the first year after application, biochar application significantly reduced GWP and GHGI by an average of 23% and 25%, respectively (Table 3). Decreases in GWP and GHGI may have been linked to increased SOC contents [23,24]. The result was consistent with [5] who conducted a similar study in upland cotton field in northwest China.…”
Section: Discussionsupporting
confidence: 79%
“…Despite limited impacts on grain yield in the first year after application, biochar application significantly reduced GWP and GHGI by an average of 23% and 25%, respectively (Table 3). Decreases in GWP and GHGI may have been linked to increased SOC contents [23,24]. The result was consistent with [5] who conducted a similar study in upland cotton field in northwest China.…”
Section: Discussionsupporting
confidence: 79%
“…A cotton study in China showed that drip irrigation, which uses less water than furrow irrigation could significantly decrease N 2 O emissions when combined with certain management practices. Drip irrigation with a plastic film mulching decreases N 2 O emissions by 36% compared to the furrow irrigation, which is mulch-free [59]. N 2 O emissions were also reduced in a rapeseed study performed in China in a sandy loam soil [88].…”
Section: Effects Of Irrigation On N 2 O Emissionsmentioning
confidence: 94%
“…For example, a study performed on cotton crops grown in heavy loam soils of Xinjian, China, showed that soils acted as a CH 4 sink under both furrow and drip irrigation, and that the degree of sequestration was dependent on season. Under drip irrigation, larger soil CH 4 uptake was observed than in furrow-irrigated fields (−2.92 kg CH 4 ha −1 under furrow irrigation versus −8.87 kg CH 4 ha −1 under drip-irrigation) [59]. Similarly, CH 4 emissions reduced up to 350 kg CH 4 ha −1 in a loam soil in Spain when sprinkler irrigation was applied to the paddy field instead of flood irrigation [68].…”
Section: Effects Of Irrigation On Ch 4 Emissionsmentioning
confidence: 94%
See 1 more Smart Citation
“…It has been widely promoted and applied since 1999, and now, the cropland covered by plastic film mulching with drip irrigation accounts for up to 80% of the total irrigated area in the Manas River Watershed. It has widely taken the place of the traditional furrow irrigation and is the predominant irrigation method in recent years in the most of China’s arid regions [ 11 ]. Additionally, the Manas River Watershed is the biggest cotton belt in Xinjiang, with a cotton-planting area of up to 52% of the agricultural land.…”
Section: Introductionmentioning
confidence: 99%